1991
DOI: 10.1177/014107689108400508
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Binaural Hearing Aids: A Cross-Over Study

Abstract: Using screening questionnaires we were able to detect individuals aged 50-65 years with hearing disability in a general practice population. Those who had better ear hearing levels of 30 dB or worse were invited to take place in a cross-over study comparing the acceptability of a monaural or binaural hearing-aid fitting. Fifty-five per cent ultimately opted for a binaural fitting and had greater hearing disability and worse mean hearing levels than those who opted for a monaural fitting. They made their choice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 5 publications
3
25
1
Order By: Relevance
“…Different methods to quantify use may lead to the different results. Studies with smaller sample sizes and a cross-over design have reported subjective preference of bilateral amplification after subjects had tried both bilateral and unilateral amplification for some time (Erdman and Sedge, 1981;Stephens et al, 1991). The responses to our survey also represent subjective outcome ratings of hearing aid provision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different methods to quantify use may lead to the different results. Studies with smaller sample sizes and a cross-over design have reported subjective preference of bilateral amplification after subjects had tried both bilateral and unilateral amplification for some time (Erdman and Sedge, 1981;Stephens et al, 1991). The responses to our survey also represent subjective outcome ratings of hearing aid provision.…”
Section: Discussionmentioning
confidence: 99%
“…The possible benefits of bilateral fitting include better speech understanding (Kobler and Rosenhall, 2002;Moore et al, 1992), in particular in noisy environments (Dreschler and Boymans, 1994;Leeuw and Dreschler, 1991;Nabelek and Mason, 1981), better sound quality (Balfour and Hawkins, 1992;Erdman and Sedge, 1981), better sound localization (Byrne et al, 1992;Dreschler and Boymans, 1994;Kobler and Rosenhall, 2002;Punch et al, 1991;Stephens et al, 1991), and improved perception of distance and movement (Noble and Gatehouse, 2006 …”
Section: Bilateral Versus Unilateral Fittingmentioning
confidence: 99%
“…In one study, only frequent users of HAs experienced better localization ability with two HAs (Chung & Stephens, 1986). Another study, comparing users of bilateral ampli cation with users of unilateral ampli cation, reported improved localization ability only for the bilateral group (Stephens et al, 1991). In connection with a study on strategies for tting bilateral HAs, this nding was supported (Puch et al 1991).…”
Section: Introductionmentioning
confidence: 93%
“…Although their research is focused on bilateral fitting strategies, they found that localization with bilateral hearing aids was significantly superior to localization with unilateral hearing aids. Besides this objective advantage, Stephens et al (1991) found that an improvement of localization was one of the reasons for people to choose for two hearing aids. Dreschler and Boymans (1994) tested localization ability with one and two hearing aids in the same subjects.…”
Section: Horizontal Localizationmentioning
confidence: 99%